The Managerial Role of The Principal in Improving Teacher Performance in the Pandemic Era (Study at Yos Sudarso Dobo Catholic High School) - Salmon T Labobar; L. Salamor; T. Gaite (IJRAEL: International Journal of Religion Education and Law, 2022)
The purpose of this research was to determine the Managerial Role of School Principals in Improving Teacher Performance in the Pandemic Era (Study at Yos Sudarso Dobo Catholic High School). Learning at Yosudarso Dobo High School since the pandemic has been conducted online, learning has been done from home, but has encountered problems in learning such as students who do not have Android phones, poor networks, no data credit, etc. Besides that, online learning has not been carried out optimally because there are several obstacles, namely teacher performance that has not been optimal in carrying out online learning. Thus the problem of teacher performance needs serious attention from the principal. The type of research used is qualitative descriptive research, the subjects in this study were 10 teachers from a total of 23 teachers, plus the vice principal of curriculum, and the principal as an informant. The results of the research found were the role of the principal in planning teacher performance that the managerial role of the principal in improving teacher performance, namely planning, implementation and evaluation of planning was needed by the principal of Yos Sudarso Dobo Catholic High School in playing the managerial role of the school by focusing on every aspect which are the basic needs of schools, namely school needs, school programs, teacher needs. The Managerial Role of the Principal in Implementing Teacher Performance that the principal conducts monitoring related to teacher performance, monitoring is carried out using WhatsApp, zoom, or via telephone in controlling the implementation of the learning process. The Managerial Role of the Principal In evaluating teacher performance that the teacher performance evaluation process carried out at Yos Sudarso Dobo Catholic High School during the pandemic period after the end of the semester and evaluation